Asia-Pacific mussel watch for emerging pollutants: Distribution of synthetic musks and benzotriazole UV stabilizers in Asian and US coastal waters - Nakata, Haruhiko (Animo Repository, 2012)
We analyzed 68 green and blue mussels collected from Cambodia, China, Hong Kong, India, Indonesia, Japan, Korea, Malaysia, Philippines, Vietnam and the USA during 2003 and 2007, to elucidate the occurrence and widespread distributions of emerging pollutants, synthetic musks and benzotriazole UV stabilizers (BUVSs) in Asia-Pacific coastal waters. Synthetic musks and BUVSs were detected in mussels from all countries, suggesting their ubiquitous contamination and widespread distribution. High concentrations of musks and BUVSs were detected in mussels from Japan and Korea, where the levels were comparable or greater than those of PCBs, DDTs and PBDEs. Significant correlations were found between the concentrations of HHCB and AHTN, and also between the concentrations of UV-327 and UV-328, which suggest similar sources and compositions of these compounds in commercial and industrial products. To our knowledge, this is the first study of large-scale monitoring of synthetic musks and BUVSs in Asia-Pacific coastal waters. © 2012 Elsevier Ltd.